Designed synthesis of stable light-emitting two-dimensional sp2 carbon-conjugated covalent organic frameworks - Enquan Jin (Nature Portfolio, 2018)
Topological connection of organic chromophores is an attractive way to design light-emitting covalent organic frameworks but the synthesis of stable light-emitting frameworks remains challenging. Here the authors report the designed synthesis of sp2 carbon conjugated frameworks that combine stability with light-emitting activity